Challenges in Implementing the Merdeka Belajar Kampus Merdeka in Higher Education - Sihombing, Humiras Betty Marlina; Panjaitan, Jelita (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Curriculum changes are a must. In fact, the very fast development of science and technology no longer supports the world of education to linger with the "comfort zone" of the applicable curriculum. Popularly known as the merdeka belajar kampus merdeka, this policy is to realize a flexible learning process, create innovative, non-restrictive learning, according to student needs, encourage students to master various sciences that are useful for entering the world, as well as provide opportunities for students to determine their subjects. the course he will take. The problems of implementing the independent learning curriculum are 1) Collaboration Mechanisms between Islamic Universities and Study Programs with External Parties, 2) Acceleration of State Universities (PTN) Go International with the policy of PTN Legal Entities (PTN-BH), 3) Internship Mechanisms Outside the Program Policy Studies internship for 3 semesters outside the study program and PT.